A systemic analysis of South Korea Sewol ferry accident – Striking a balance between learning and accountability. (March 2017) - Kee, Dohyung; Jun, Gyuchan Thomas; Waterson, Patrick; Haslam, Roger
Abstract: The South Korea Sewol ferry accident in April 2014 claimed the lives of over 300 passengers and led to criminal charges of 399 personnel concerned including imprisonment of 154 of them as of Oct 2014. Blame and punishment culture can be prevalent in a more hierarchical society like South Korea as shown in the aftermath of this disaster. This study aims to analyse the South Korea ferry accident using Rasmussen's risk management framework and the associated AcciMap technique and to propose recommendations drawn from an AcciMap-based focus group with systems safety experts. The data for the accident analysis were collected mainly from an interim investigation report by the Board of Audit and Inspection of Korea and major South Korean and foreign newspapers. The analysis showed that the accident was attributed to many contributing factors arising from front-line operators, management, regulators and government. It also showed how the multiple factors including economic, social and political pressures and individual workload contributed to the accident and how they affected each other. This AcciMap was presented to 27 safety researchers and experts at 'the legacy of Jens Rasmussen' symposium adjunct to ODAM2014. Their recommendations were captured through a focus group. The four main recommendations include forgive ( no blame and punishment on individuals), analyse (socio-technical system-based), learn (from why things do not go wrong) and change (b ottom-up safety culture and safety system management ). The findings offer important insights into how this type of accident should be understood, analysed and the subsequent response.